Novel approaches for the assembly simulation of rigid Skin Model Shapes in tolerance analysis. (August 2018) - Schleich, Benjamin; Wartzack, Sandro
Abstract: While the modelling of nominal assemblies is sufficiently solved in modern computer-aided design tools, the assembly simulation for parts considering geometrical deviations is still an important research issue. Particularly in tolerance analysis, the assessment of the effects of geometrical part deviations on the part assembly behaviour is of central importance. Though established assembly simulation approaches for parts with geometrical deviations cover a moderate range of real assembly problems, they are not suitable for all assembly simulation problems. To overcome this shortcoming, a general framework and new approaches for the assembly simulation of Skin Model Shapes for the use in tolerance analysis are presented. The application of these assembly simulation approaches is highlighted in generalized case studies and recommendations for their use in tolerance simulations are derived. Highlights: A general assembly simulation framework for Skin Model Shapes is introduced. The framework is applied to two typical tolerance analysis case studies. Important insights and recommendations for the use of the framework are derived.